Electrocatalytic Reduction of Carbon Dioxide to Carbon Monoxide by a Polymerized Film of an Alkynyl‐Substituted Rhenium(I) Complex. Issue 7 (12th April 2013) - Portenkirchner, Engelbert; Gasiorowski, Jacek; Oppelt, Kerstin; Schlager, Stefanie; Schwarzinger, Clemens; Neugebauer, Helmut; Knör, Günther; Sariciftci, Niyazi Serdar
Abstract The alkynyl‐substituted ReI complex [Re(5, 5′‐bisphenylethynyl‐2, 2′‐bipyridyl)(CO)3Cl] was immobilized by electropolymerization onto a Pt‐plate electrode. The polymerized film exhibited electrocatalytic activity for the reduction of CO2 to CO. Cyclic voltammetry studies and bulk controlled‐potential electrolysis experiments were performed by using a CO2‐saturated acetonitrile solution. The CO2 reduction, determined by cyclic voltammetry, occurs at approximately −1150 mV versus the normal hydrogen electrode (NHE). Quantitative analysis by GC and IR spectroscopy was used to determine a Faradaic efficiency of approximately 33 % for the formation of CO. Both values of the modified electrode were compared to the performance of the homogenous monomer [Re(5, 5′‐bisphenylethynyl‐2, 2′‐bipyridyl)(CO)3Cl] in acetonitrile. The polymer formation and its properties were studied by using SEM, AFM, and attenuated total reflectance (ATR) FTIR and UV/Vis spectroscopy.